STANDARISASI PARAMETER SPESIFIK EKSTRAK METANOL BIJI KEBIUL (CAESALPINIA BONDUC L.) SEBAGAI BAHAN BAKU OBAT HERBAL TERSTANDAR - Mustapa, Mohammad Adam; Abdulkadir, Widy Susanti; Halid, Indriany Femina (Journal Syifa Sciences and Clinical Research, 2020)
The determination of specific parameters standardization of knicker nut (Caesalpinia BonducL.) methanol extract as the standardized herbal medicine raw materials has been carried out to ensure the quality improvement of traditional medicines and the efficacy of the plant. The purpose of this research is to determine the specific parameters of knicker nut extract so that it can be consumed as herbal medicines that have been scientifically tested. The knicker nut extract was obtained from the extraction employing the maceration method with methanol as the solvent. Specific parameters testing included extract identity, extract organoleptic, dissolved compound in certain solvents, along with extract chemical test. The results of extract identity testing show that the Latin name is CaesalpiniaBonducL. with the nut as the used part of the plant. The organoleptic test reveals that the plant is in the form of thick extract, blackish-brown in color, bitter, has pungent smell/typical smell of knicker nut, contains water-soluble compound of 10.33% with the standard deviation ±1.154707755, N-hexane-soluble compound of 3.33% with the standard deviation ±1.154707755, and methanol-soluble compound of 17.33% with the standard deviation ±3.511886957. Moreover, the flavonoids wavelengths are 382 nm (band I) and 262 nm (band II).